(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تم دراسة التزنخ الاوكسيدي في كريمات التجميل بطريقة انتقائية, سهلة, لا تتأثر بلون المادة المدروسة وذات دقة وحساسية جيدتين هي طريقة التحليل الاستقطابي (المعايرة الأمبيرومترية) والتي تراوح فيها الانحراف المعيـاري النسبي بيـن (1.10 - 2.90) %, حيث قدرنا بواسطتها الرقــم البيروكسيدي لـــــ90 عينة من الكريمات على اختلاف أنواعها (كريمات منظفة حليبية – كريمات واقية شمسية – كريمات مغذية وكريمات الأساس) ما بين منتجات محلية ومستوردة, وقارنا النتائج التي حصلنا عليها باستخدام المعايرة اليودومترية الكلاسيكية بواسطة ثيوسلفات الصوديوم كمرجع ومطبوخ النشاء كمشعر والتي تراوح فيها الانحراف المعياري النسبي بين( 2.90 – 5.50) %, وقد وجدنا أن متوسط رقم البيروكسيد للمنتجات المحلية كان أكبر منه في المنتجات المستوردة, وأن ما يعادل 8 % من المنتجات المحلية غير صالحة للاستعمال في حين أن 17.50 % من المنتجات المستوردة كانت كذلك أيضاً. A study of Oxidative Rancidity in Cosmetic Creams has been done, using polarizing analysis (A mperometric calibration) which is a selective and easy way not affected by the colour of the studied material, and of high accuracy and sensitivity. The Relative Standard Deviation ranges between (1.10 - 2.90 )%, through which we could estimate the Peroxide Values in 90 Samples of the various kinds of Creams: (Milk Cleansing Creams - Sunscreen Creams - Nutrient Creams - Foundation Creams) for the imported and locally produced Creams. We have compared among the results obtained by applying the classical Iodometric Calibration through Sodium Thiosulfate and Cooked Starch as an Indicator where the Relative Standard Deviation ranges between (2.90 - 5.50) %. We have found that the Average Peroxide Value in the local products was higher than in the imported products, and about 8 % of the local products were not fit for use, while 17.50 % of the imported products were not fit as well.